A Machine Learning-based Approach for Intrusion Detection and Prevention in Computer Networks - Dubey, Bhanu Prakash (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The potential of cyberattacks and network penetration has increased due to modern enterprises' increasing reliance on computer networks. Such attacks are detected and prevented by intrusion detection and prevention systems (IDPS), although conventional rule-based solutions have difficulties identifying unidentified attacks. Due to its capacity to learn from data and spot patterns of assault that conventional methods could miss, machine learning (ML) techniques have been gaining prominence in IDPS. This article provides a thorough analysis of the several ML methods utilized in IDPS, including supervised, unsupervised, and hybrid techniques. Also, a hybrid ML-based IDPS that combines the advantages of several methodologies for better performance is proposed. Furthermore, covered are the difficulties with ML-based IDPS and potential solutions. It is demonstrated how ML-based IDPS may be applied in real-world situations, emphasizing the advantages of applying ML to intrusion detection and prevention. In conclusion, this study offers insights into the most recent methods for ML-based IDPS and their potential to enhance network security.